Constructing Digital Financial Trust in SMEs within Emerging Economies: A Grounded Theory Study - Baidowi, Muhammad (Universitas 17 Agustus 1945 Surabaya, 2026)
The rapid expansion of digital financial services has transformed the financial landscape for small and medium-sized enterprises (SMEs), particularly in emerging economies. Despite increased accessibility, the issue of trust remains a critical barrier to the effective adoption and sustained use of digital financial platforms. Existing studies have largely approached trust from a quantitative or technology acceptance perspective, offering limited insight into how trust is socially constructed and experienced by SMEs in practice. Addressing this gap, this study employs a grounded theory approach to explore the processes through which SMEs construct digital financial trust within complex and often uncertain institutional environments. Drawing on in-depth interviews and iterative data analysis, this research develops a process-based theoretical model that explains how trust emerges through the interplay of experiential learning, social influence, perceived risk negotiation, and platform interaction. The findings reveal that digital financial trust is not a static attribute but a dynamic and contextually embedded process shaped by both technological affordances and socio-institutional conditions. SMEs actively negotiate trust by balancing perceived benefits with concerns over security, transparency, and reliability, while leveraging peer networks and prior experiences to reduce uncertainty. This study contributes to the literature by advancing a grounded, process-oriented understanding of digital financial trust, extending beyond dominant adoption models. It also offers practical implications for policymakers, fintech providers, and development institutions seeking to enhance financial inclusion and digital transformation among SMEs in emerging economies.